Analisis Resiko Ergonomi Pengolahan Tanah Menggunakan Traktor Tangan dengan Nordic Body Map (NBM) - Anggraini, Nurvita; Suharyatun, Siti; Rahmawati, Winda; Warji, Warji (abe.fp.unila.ac.id, 2025)
Continuous tillage using hand tractors requires high physical strength and involves non-ergonomic body postures. Work involving heavy physical activity, especially with improper working postures can cause musculoskeletal injuries or musculoskeletal disorders/ MSDs). This study aims to identify the level of musculoskeletal disorders (MSDs) of hand tractor operators in tillage using the Nordic Body Map (NBM) method. The study was conducted in Banjar Agung Village, East Lampung, involving operators aged 30–40 years and operators aged 40–50 years. Data were obtained through interviews to fill out the NBM questionnaire. The results of the NBM analysis showed that tillage activities using two-wheeled tractors by operators aged 30–40 years did not require immediate treatment with a Likert scale of 1 (light risk level) and that by operators aged 40–50 years required immediate treatment with a Likert scale of 2 (high risk level). Keywords: Hand Tractor, Nordic Body Map (NBM), Musculoskeletal Disorders (Msds), Soil Tillage.